Cross-Dysregulation of O-GlcNAcylation and PI3K/AKT/mTOR Axis in Human Chronic Diseases - Very, Ninon (Front Endocrinol (Lausanne), 2018)
The hexosamine biosynthetic pathway (HBP) and the phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathway are considered as nutrient sensors that regulate several essential biological processes. The hexosamine biosynthetic pathway produces uridine diphosphate N-acetylglucosamine (UDP-GlcNAc), the substrate for O-GlcNAc transferase (OGT), the enzyme that O-GlcNAcylates proteins on serine (Ser) and threonine (Thr) residues. O-linked β-N-acetylglucosaminylation (O-GlcNAcylation) and phosphorylation are highly dynamic post-translational modifications occurring at the same or adjacent sites that regulate folding, stability, subcellular localization, partner interaction, or activity of target proteins. Here we review recent evidence of a cross-regulation of PI3K/AKT/mTOR signaling pathway and protein O-GlcNAcylation. Furthermore, we discuss their co-dysregulation in pathological conditions, e.g., cancer, type-2 diabetes (T2D), and cardiovascular, and neurodegenerative diseases.